Microchannel miter bend effects on pressure equalization and vortex formation - Taniselass, S.; Retnasamy, Vithyacharan; Poopalan, Prabakaran, Prof. Madya Dr. (Springer-Verlag, 2011)
Link to publisher's homepage at http://www.springerlink.com/